LADS Survey - A Case Study on Australia’s Northwest Shelf - Sinclair, Mark (The International Hydrographic Review, 2002)
Laser Airborne Depth Sounder (LADS) systems provide an accurate, rapid and cost effective method of surveying coastal areas. These systems have been used by governments and commercial organisations over the last decade to conduct surveys for nautical charting, coastal zone management, territorial sea baseline determination, offshore exploration and defence applications. In the field of offshore exploration commercial LADS surveys have been used to provide high definition bathymetric data to support 3D seismic data collection in poorly surveyed shallow areas. This paper describes the conduct of a LADS Mk II survey for the oil and gas industry on Australia’s Northwest Shelf and the quality control procedures undertaken.